INTERNATIONAL ISLAMIC ECONOMIC SYSTEM CONFERENCE (I-iECONS 2021) - Buchori, Nur Syamsudin; Juhary, Ali; Aslam, Mohd Mizan (2021)
The COVID-19 pandemic has a significant influence on world economic growth, including Indonesia, which had an impact on the outflow of foreign funds that reached Rp. 153.7 trillion from the stock market, SBN, SBI from January to April 2020. Almsgiving will derive to economic balance, where zakat, infaq, and sadaqah will create a transfer of consumption from people who are well off to people in need so that it can generate aggregate supply and demand. The lack of obtaining zakat, infaq, sadaqah and waqf in Bekasi City which is less than 1% of the potential indicates a weakness in Amil Zakat management, so it is necessary to find a model for the effectiveness of collecting and utilizing zakat that will make the enormous potential can be realized. This study is aim to find a model for the collection, distribution, and utilization of Zakat, Infaq, and Sadaqah in Bekasi City. This study is using qualitative descriptive approach to describe, explain, and interpret the collected data which obtained from Bekasi City in Figures 2020 report (BPS Kota Bekasi 2020). The potential of the ZIS funds used a strategic role model for managing Amil Zakat in Bekasi City with a four-dimensional approach: 1) Islamic social finance (Zakat, Infaq, and Sadaqah); 2) service process; 3) Muzaki loyalty; 4) Amil's human resources. These four dimensions are the strategic needs of the Amil Zakat Institute, Islamic Social Finance to discuss potential sources of Zakat, Infaq, and Sadaqah that will be channeled through programs that have an impact on the development of Bekasi City. The explanation in this research is expected to be a driving force to achieve the maximum collection, distribution, and utilization of ZIS in Bekasi City in realizing its potential.